Indeks dan status kesuburan pada tanah di daerah aliran sungai (DAS) rejoso pasuruan - Amanda Aradea Sufla (Fakultas Pertanian, 2026)
The soil fertility index is a determination of the level of soil fertility that is able to provide nutrients for plants in sufficient quantities. This research was conducted in the Rejoso River Basin (DAS) which administratively borders directly with Malang and Probolinggo Regencies with the aim of analyzing the value of the soil fertility index. This value is obtained by analyzing the chemical properties of the soil including the parameters of pH, Nitrogrn (N), Phospor (P), Potassium (K), C-Organic, CEC, Calcium (Ca), Sodium (Na), Magnesium (Mg), and KB. The analysis was carried out using the Soil Fertility Index (SFI) and Principal Component Analysis (PCA) methods. The results of the study indicate that there are differences in the value of the soil fertility index in each Land Map Unit (SPL) in the Rejoso Watershed. The data obtained from this study are expected to be used to design better soil management strategies.
Finalisasi Rudy K
Keywords: ANOVA Test; Chemical Properties; PCA Analysis; SFI; Watershed.